Metode Waterfall untuk Implementasi Sistem Informasi Pengajuan Uji SNI Produk dan Kalibrasi - Muhammad Muhammad; Sinta Maria; Mukhtar Mukhtar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
The submission of SNI product testing and calibration is a crucial process to ensure the quality and compliance of products and measuring instruments with applicable standards. However, the submission process at BSPJI Pekanbaru is still conducted manually, leading to several issues such as delayed services, data entry errors, and lack of transparency in information. This study aims to design and develop a web-based information system to facilitate the online submission of SNI product testing and calibration. The system development method used is the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. Data was collected through observation, interviews, and literature review. The developed system includes features such as online submission, status tracking, test scheduling notifications, and result verification. The findings show that this system improves the efficiency of submission processes, reduces manual workload, and enhances real-time access to information for customers. This digital solution is expected to improve the quality of public services at BSPJI Pekanbaru.